Gas to liquids from biogas and landfill gases - Zamri M.F.M.A.; Bahru R.; Fattah I.M.R. (Elsevier, 2025)
Landfilling is a widely established method for waste disposal, particularly in underdeveloped countries. Although it is classified as the final approach in the waste management hierarchy, sanitary landfills remain crucial. Landfills are designed to manage leachate, landfill gas, and odors and are equipped with facilities that protect the environment to prevent future problems. However, there is potential for waste valorization and bioenergy product development from landfill systems that can be explored and utilized. This chapter provides an overview of landfill design and operation, followed by a discussion on how to valorize landfill waste, specifically the conversion of landfill gas into liquid form for bioenergy utilization. Finally, the chapter concludes with a summary of the main points covered. ? 2024 Elsevier Ltd. All rights reserved.